How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10616734 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1008 ZenodoArchiveConcept: 10616733
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH